Ways of Further Development of Marketing Management Elements in "Sam Antep Gilam" LLC - Usmanov I. A. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In this article, the creation of a new product in the enterprise, the study of the market capacity in relation to this type of product, the creation of a new type of product, paying special attention to the reduction of product costs, and the maximum efficiency of internal logistics are considered.